The framework governing the reception of international arbitration awards in Algeria - Bouselsal, Noureddine (Journal of Human Sciences, 2022)
This survey examines the algerian legal framework regulating the reception of international arbitration awards, and seek whether this framework is behind the fears of foreign parties to come to Algeria for requesting the enforcement of arbitration awards. We will deal with the various points relating to this field via studying the recognition systems, enforcement of arbitration awards (1), and the ways the international arbitration awards can be appealed according to the algerian legislator through eliminating some traditional ways of appeal, and adopting ways of appeal that suit the specificity of international commercial arbitration (2).